Community’s misconception about COVID-19 and its associated factors among Gondar town residents, Northwest Ethiopia - Habtamu Sewunet Mekonnen; Abere Woretaw Azagew; Chalachew Adugna Wubneh; Getaneh Mulualem Belay; Nega Tezera Assimamaw; Chilot Desta Agegnehu; Telake Azale; Zelalem Nigussie Azene; Mehari Woldemariam Merid; Atalay Goshu Muluneh; Demiss Mulatu Geberu; Getahun Molla Kassa; et al. (Tropical Medicine and Health, 2020)
Abstract Background Despite the implementation of various strategies such as the declaration of COVID-19 emergency state, staying at home, lockdown, and massive protective equipment distribution, still COVID-19 is increasing alarmingly. Therefore, the study aimed to assess the community’s perception of COVID-19 and its associated factors in Gondar town, Northwest Ethiopia. Methods A community-based cross-sectional study was employed among 635 Gondar administrative town residents, from April 20 to April 27, 2020. Study participants were selected using a cluster sampling technique. Data were collected using an interviewer-administered structured questionnaire. Epi-Data version 4.6 and STATA 14 were used for data entry and analysis, respectively. Logistic regressions (bivariable and multivariable) were performed to identify statistically significant variables at p < 0.05. Results Of the 635 study participants, 623 have completed the study with a 98.1% response rate. The mean age of participants was 36.32 years (SD ± 13.24). The overall magnitude of the community’s misconception about COVID-19 stood at 56.9% (349). Age and religion showed a negative association with misconceptions. To be specific, being in the age group of 27–33 (AOR = 0.52, 95% CI 0.32, 0.86) and being a Muslim (AOR 0.51, 95% CI 0.34, 0.78) were negatively associated with the misconception of COVID-19, whereas occupation and awareness showed positive associations with the misconception. To be specific, having an unemployed occupational status (AOR = 1.79, 95% CI 1.14, 2.82) and being unaware of the number of cases of COVID-19 (AOR 1.66, 95% CI 1.05, 2.62) were positively associated with the community’s misconception on COVID-19. Conclusion The magnitude of the community’s misconception about COVID-19 among Gondar town residents was high. Age, religion, unemployment, and unawareness about the number of COVID-19 cases were significant factors of misconception about COVID-19. Thus, stakeholders ought to build community perceptions about COVID 19. To resolve misinformation about COVID-19, accurate and relevant information should be provided to the community using appropriate communication media.